DYNAMICS OF BODY ROLLING IN THE CASE OF STEADY MOTION - Bosov, A. A.; Ilman, V. M. (Science and Transport Progress, 2004)
This article offers you the analysis of dynamics of moving rolling element along horizontal deforming base. For rolling, like O. Reinolds, was found the conditions of steady rolling of element and was demonstrated, that the rolling without towing and slipping are possible.